Comparison of Mandelshtam’s Conditions with Convergence Conditions for Iterative Procedures in the Analysis of Complex Dynamic Systems by Means of Partial Models - Stańczyk, T.L. (Engineering Transactions, 1992)
The convergence conditions for iterative procedures in the analysis of dynamic systems with the use of partial models are compared with Mandelshtam’s conditions (uncoupling of vibrations of partial models). Both basic iteration procedures are discussed. The conditions for iterative procedures are found to be much weaker than those formulated by Mandelshtam. A simplified criterion for the selection of the type of procedure a manner in which a system is to be decomposed is presented.